Determining the precursors of boredom - Dagami, Michelle Marie C (Archīum Ateneo, 2011)
This paper presents analysis of user action log files and human observation data gathered from students using Aplusix. The objective of the study is to determine the precursors of student boredom, an affective state that is negatively correlated with learning. The researchers matched the action logs with the humancoded observation by using the time window synchronization technique. The researchers segregated the data into bored and non-bored time windows. The researchers then compared the features of these sets, e.g. frequency of different actions (i.e. hit of a key, special keys and arrow keys) and average duration between actions. The analysis identified three probable precursors of boredom: frequent use of the ask for solution, ask for verification and ask for score, rare use of the Number keys and rare use of the Special buttons.